VOLATILE COMPOUNDS IN STINKHORN (PHALLUS IMPUDICUS L. EX PERS.) AT DIFFERENT STAGES OF GROWTH - Pudil, Frantisek; Uvira, Roman; Janda, Vaclav (European Scientific Journal, ESJ, 2014)
Volatile compounds released from stinkhorn (Phallus impudicus L. ex Pers.) at its different stages of maturity (immature “egg” form, mature fruit body, over-ripe fruit body) were examined. A total number of 59 components were identified with the use of headspace solid-phase microextraction (HS-SPME) method followed by gas chromatography-mass spectrometry (GC-MS). The research showed a considerable qualitative difference of major components, according to their stages of maturity. Dimethyl trisulfide, cis-β-ocimene, trans-β-ocimene, 2-phenylacetladehyde and 2-phenylethanol were the most abundant volatiles in mature fruit bodies. Dimethyl oligosulfides, the most significant contributors to the strong and foul odor of stinkhorn fruit bodies, were absent at egg-shaped and over-ripe stages.